(untitled) (LACCEI, 2024)
In recent years, the planet is being affected by environmental pollution from petroleum residues such as used lubricating oils, which originate from the lubricating oil of various commercial brands used by vehicles, industrial machines, among others, which when used they lose their physical and chemical characteristics that cause contaminants in their composition such as sulfur, heavy metals, water, etc. In the present study, the performance of biodegradation of used lubricating oil will be compared, using the Oil Eating Microbes (OEM) bacterial consortium made up of three bacteria (Rhodococcus, Pseudomonas and Bacillus), which quantified the percentage of biodegradation of total hydrocarbons. of petroleum contained in the bentonite clay Tonsil 166, from two experimental tests, whose optimum result was a percentage of biodegradation of 57%, at Temperature = 35 ºC, pH = 7.0, mechanical agitation = 120 RPM, dilution of the clay contaminated with used lubricating oil in water of 1(clay):3(water).